Editorial 2021: Letter from the Board of the Journal of Sylva Indonesiana (JSI) - Nuryawan, Arif; Heri Iswanto, Apri (Journal of Sylva Indonesiana, 2021)
This letter is a second editorial in the fourth year of Journal of Sylva Indonesiana (JSI)’s establishment. This editorial contains messages from the boards, comprised of a former and a chief editor of this journal, about development of this journal, statistics of the published articles, acknowledgment, and closing remarks. JSI has been accredited by Ministry of Research and Technology, Republic of Indonesia with third rank (Sinta 3) since first volume of the publication. During the development of this journal, 25 scientific articles and 1 editorial have been published with peer-reviewed. Classification according to aim and scope of this journal resulted in study field of sylviculture as the major (20%) of forestry and natural resources theme, while the other fields maintained their relative portion. Acknowledgments have been conveyed to contributors of this journal (authors, reviewers, editors, publishers, and readers). Closing remarks were consisted of condolence news, a glimmer of hope to return a normal post pandemic situation, and of course a wish all contributors a very happy, healthy and successful year of 2021.